1993
DOI: 10.1111/j.1525-1594.1993.tb00623.x
|View full text |Cite
|
Sign up to set email alerts
|

The Significance and Prevention of Air Emboli with the Total Artificial Heart

Abstract: Embolism remains a significant complication of the total artificial heart (TAH). The ineffectual deairing of the TAH can allow embolization of the retained air. The standard needle aspiration of TAH air (Group A) was compared with a new protocol (Group B) that included standard needle TAH aspiration plus simultaneous pumping of the TAH against an occluded ascending aorta and main pulmonary artery with vacuum applied to a needle in the proximal aorta and pulmonary artery. There were 4 calves in each group. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…During work with total artificial hearts, Murray et al 10 identified small, chronic fibrotic scars, without evidence of acute infarction in the kidneys of 50% of calves (4/8) with the Utah 100 and Jarvik 7 total artificial hearts after 12 days of support. The average number was three lesions per animal, and each lesion was less than or equal to 6 mm in diameter at the cortex.…”
Section: Resultsmentioning
confidence: 98%
“…During work with total artificial hearts, Murray et al 10 identified small, chronic fibrotic scars, without evidence of acute infarction in the kidneys of 50% of calves (4/8) with the Utah 100 and Jarvik 7 total artificial hearts after 12 days of support. The average number was three lesions per animal, and each lesion was less than or equal to 6 mm in diameter at the cortex.…”
Section: Resultsmentioning
confidence: 98%
“…1,5 Air embolism remains a significant complication of the total artificial heart, caused by ineffectual de-airing of the blood pump, which allows embolization of the retained air. 2 The entrained air may cause immediate issues, such as a drop in pump pressure rise, flow rate, and power, especially if more air than the impeller can handle is entrapped. This may cause air cavitation and impeller rubbing that in turn may damage the impeller surface and make pump biocompatibility a concern.…”
Section: Discussionmentioning
confidence: 99%
“…The negative effects of air deposition into the circulatory system such as multi-organ functional deterioration have been previously reported in the literature. 1,2 The current techniques of de-airing and prevention of air entrapment are limited to basic attempts of careful device-to-conduit connection, priming of connection lines, and proper device manipulation to avoid excessive air engagement into circulation during connection. These techniques are imperfect, and the risk of air embolism remains since the access to atmospheric air is never fully limited during the actual device-to-conduit connection process.…”
Section: Introductionmentioning
confidence: 99%
“…Protamine was administered to reverse the systemic heparinization, per our standard protocol. The chest was closed, and the animal was transferred to a chronic care unit for postoperative monitoring . After termination of each experiment, the animals were sacrificed, and thorough muiltiorgan analyses and post‐explant pump evaluations were performed in all cases.…”
Section: Methodsmentioning
confidence: 99%